Comparative evaluation of norovirus infection in children with acute gastroenteritis by rapid immunochromatographic test, RT-PCR and real-time RT-PCR - Kattareeya Kumthip (2018)
© The Author [2017]. Published by Oxford University Press. All rights reserved. Immunochromatographic (IC) test for norovirus detection is a rapid and simple detection method. This study evaluated the sensitivity and specificity of a recent version of R-Biopharm RIDAVR QUICK Norovirus IC assay for norovirus detection in fecal specimens from children hospitalized with acute gastroenteritis. Fecal specimens were tested by IC kit in comparison with gold standard reverse transcription polymerase chain reaction (RT-PCR) and real-time RT-PCR. The IC kit showed high sensitivity and specificity comparable with PCR-based methods. None of false positive and false negative was found and the assay did not cross-react with other gastroenteritis viruses. The IC assay could detect genogroup I.5 (GI.5) and a wide range of genotypes in the GII noroviruses including GII.3, GII.4, GII.6, GII.7, GII.14, GII.15, GII.21, and also newly emerging GII.17 norovirus. In conclusion, this norovirus IC kit could be an alternative choice for rapid screening or a quick diagnostic tool for norovirus detection in fecal specimens of acute gastroenteritis patients.